LITERATURE OF REVIEW THE INFLUENCE OF EMPLOYEE JOB SATISFACTION ON EMPLOYEE COMPENSATION AND JOB CHARACTERISTICS (Production Department of PT. XYZ) - Dewi Puspaningtyas Faeni; Azril Hikmal Arsya (Draf Solusi Indonesia, 2024)
A literature review regarding the impact of job satisfaction on employee pay and job features is examined in this study. The production section is the subject of research carried out at PT XYZ. The influence of two independent factors and one dependent variable will be the main topic of this research. This research uses quantitative methodology and data collection using questionnaires. SPSS 28 for Windows is the application used in this research to analyze research data.